P-196 Exploring the quality of the dying and death experience in the emergency department: a review. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - McCallum, Kay; Jackson, Debra; Walthall, Helen; Aveyard, Helen
Abstract : Background: Patients attend the emergency department (ED) for a variety of reasons. Unfortunately some of these patients will not survive. Little is known about how staff and particularly carers experience being with a dying patient in this setting (Bailey, Murphy & Porock, 2011; Chan, 2011; Decker, Lee & Morphet, 2015). The aim of this review was to examine the quality of dying and death in the ED from the perspective of staff and carers. Method: A systematic search of MEDLINE, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), AMED, Magonline (internurse), EMBASE and the Cochrane library was undertaken during February –August 2017. Fourteen articles fit the inclusion criteria (papers published in the English language between 1995–2017) for this review. Findings and discussion: The over-arching theme that emerged is that care in the ED is focused on living not dying. Because the ethos is about saving lives, those whose lives cannot be saved can be marginalised or side-lined, leading to a potentially poorer experience for the relatives and friends (carers) (Bailey, Murphy & Porock, 2011). Further themes included staff stress and distress, and the difficulty of meeting the needs of the carers in this environment. Carers felt the staff had no time for them and that communication was generally poor (Bailey, Murphy & Porock, 2011). However, there are minimal studies that asked the views of the carers and this is therefore an area in which further research is needed. Implications for research and practice: Findings suggest that there remains a gap in knowledge around the quality of dying and death in the ED from the perspective of carers of the dying patient. Supporting staff in the ED to care effectively for patients who are dying whether from acute or non-acute causes is paramount.